3D #DigitalInvasions: a crowdsourcing project for mobile user generated content. Issue 2 (2015) - Bonacini, Elisa; Inzerillo, Laura; Marcucci, Marianna; Santagati, Cettina; Todisco, Fabrizio
No abstract available